Fashions in Monastic Endowment: the Foundations of the Clare Family, 1066–1314 - Ward, J. C. (The journal of ecclesiastical history, 1981)
The great expansion in monasticism in Normandy and England in the eleventh and twelfth centuries is a commonplace of medieval history, as is the marked diminution in monastic grants after c. 1200. Far more attention, however, has been paid to the religious houses than to their founders, and it is only by looking at a baronial family over a long period that one can discern the fashions which undoubtedly existed in monastic benefaction and the changes in attitude of successive generations. The Clare family were both long-lasting and prolific, and, because of the numerous changes in the landed position of various members of the family, it is possible to see how closely in the eleventh and twelfth centuries the acquisition of new territories and the endowment of monasteries went together. Moreover, we are able to trace the changing preferences for different monastic orders and, to some extent, the reasons for this, and, in addition, to see this in the context not only of Normandy and England, but of Wales and Ireland as well. Whereas in the eleventh and early twelfth century, the Clares' gifts passed to Benedictine houses, many of them Norman or with Norman connections, they became more interested later in the new orders of the Augustinian canons and Cistercians which were spreading rapidly over Europe. At the same time they made grants to the military orders of the Hospitallers and Templars which, by giving knights the opportunity to combine fighting with a monastic life, fused two ideals of the twelfth-century world. In contrast to the variety and amount of these monastic benefactions, the Clares were content in the thirteenth century to make only the occasional grant, but they were insistent on maintaining their rights of patronage. In addition, their interest turned to the new orders of friars. There is, however, no indication here of continuous family interest from one generation to the next as would have been the case in the early twelfth century.